Physics teachers’ perspectives of roles of mathematics in physics learning in senior high schools - Fitria Amalia, Irma; Andriani, Dini; Adimayuda, Rizal (Insitut Pendidikan Indonesia, 2024)
This study explores senior high school physics teachers’ perspectives on the role of mathematics in physics education. Through qualitative interviews with five experienced teachers, this research investigates how mathematics supports students’ understanding of physics concepts, as well as the challenges teachers face in integrating it effectively. Findings reveal that teachers view mathematics as essential for deepening comprehension, enabling students to analyze, predict, and quantify physical phenomena. However, they also acknowledge the difficulties that students, especially those with weaker math skills, encounter, which can lead to disengagement. To address this, teachers employ adaptive strategies, such as starting with conceptual explanations and using visual aids and real-world examples to make mathematics more accessible. These insights underscore the need for a balanced approach that integrates mathematics in ways that align with students’ cognitive readiness, thereby enhancing engagement and comprehension. This study contributes to understanding effective instructional practices in physics education, supporting more accessible and meaningful learning.